Lipophilic profile of the edible halophyte Salicornia ramosissima - Isca, Vera M. S. (2017)
Salicornia ramosissima J. Woods is considered, in the Iberian Peninsula and France, a gourmet product. Nevertheless, is one of the less studied Salicornia species. In this work, GC-MS was employed to, for the first time; fully characterise the lipophilic profile of S. ramosissima and to assess the effect of natural and extra irrigation in that profile. The obtained data showed esterified and free fatty acids, fatty alcohol, sterols, alkanes and aromatic acid derivatives, being palmitic acid, tetracosanol and octacosanol the most abundant compounds. The extra irrigation increases significantly (P < 0.001) the content of esterified lipophilic compounds. Stigmastanol, 24-ethyl-δ(22)-coprostenol, several secondary fatty alcohols and dicarboxylic acids were identified for the first time in Salicornia genus. Several of the detected compounds are known to have health benefits and our results suggest that S. ramosissima should be considered as an important dietary source of lipophilic phytochemicals.